VITAMIN D ACROSS THE LIFE SPAN - Pavlović, Dragan M.; Pavlovic, Aleksandra M. (Specijalna edukacija i rehabilitacija, 2013)
Vitamin D is a secosteroid hormon with pleiotrophic functions and essential for normal development and health throughout the entire life span. Vitamin D deficiency has epidemic proportions worldwide and interferes with important metabolic processes. Its prevalence is estimated in various populations of different etnicity and age from 50% up to 100% in certain groups. The main source of vitamin D for men is skin production by ultraviolet B radiation acting on 7-dehydrocholesterol. This is cholecalciferol or vitamin D3. Less than 20% is obtained from food. The active form, 1,25-dihydroxy-vitamin D (calcitriol) is synthesized in the kidney. Synthetic capacity declines with ageing. The main function of vitamin D is calcium homeostasis important for musculosceletal health, innate immunity, arterial integrity, endocrine function,  antiinflamation, and various local processes (autocrine and epicrine functions) in more than 30 tissues where receptors exist. Vitamin D is also important for cognitive function, mainly executive in the frontal lobe. Normal vitamin D levels are above 75 nmol/L. Vitamin D deficiency is mostly due to the lack of sun exposure but can also be secondary to some individual characteristics. Deficiency during intrauterine development can lead to early and late negative consequences in bone growth, immune system, and cognition. The extreme deficiency causes rikets. In adults vitamin D deficiency has been suggested as a risk factor for infectious and autoimmune diseases, carcinomas (especially of the breast and colon), multiple sclerosis, falls, osteoporosis, bone fractures, cardiovacular and cerebrovascular diseases, diabetes mellitus type I and II, infertility, cognitive decline and dementia. Oral supplementation with serum level normalization can lead to reduction of these risks but even amelioration of some pathological states. Recomendation ranges form 400 IU of vitamin D in infants to 2000 IU in older population, but it should be guided by individual clinical circumstances. Key words: Vitamin D, cognition, immunity, ultraviolet B radiation